2011
DOI: 10.1039/c1sm05057e
|View full text |Cite
|
Sign up to set email alerts
|

Imaging magnetic flux lines with iron oxide nanoparticles using a “fossilized liquid assembly”

Abstract: Directed self-assembly of nanomaterials via external fields is an attractive processing tool for industry as it is inherently inexpensive and flexible. Direct observations of this process are however challenging due to the nano and meso length scales involved. The self-assembly of magnetic nanoparticles in particular has gained much recent interest for applications ranging from biomedical imaging and targeted cancer therapy to ferrofluid mechanical damping devices, that rely on the state of aggregation and ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our previous studies have demonstrated the effect of the magnetic field strength and the average nanoparticle agglomeration area and morphology when organized at an oil–water liquid–liquid interface by a method termed “Fossilized Liquid Assembly (FLA)”. , By removal of one (water) liquid phase, and embedding the particles in the other (oil) phase by its polymerization with UV light, such nanostructures protruding from the air/film surface were observed under an applied magnetic field. The shape and the morphology of such magnetic field induced agglomerate structures can also decrease the total Gibbs energy of the system at the liquid–liquid interface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated the effect of the magnetic field strength and the average nanoparticle agglomeration area and morphology when organized at an oil–water liquid–liquid interface by a method termed “Fossilized Liquid Assembly (FLA)”. , By removal of one (water) liquid phase, and embedding the particles in the other (oil) phase by its polymerization with UV light, such nanostructures protruding from the air/film surface were observed under an applied magnetic field. The shape and the morphology of such magnetic field induced agglomerate structures can also decrease the total Gibbs energy of the system at the liquid–liquid interface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In an external magnetic field the magnetic moments of individual particles orient along the field lines, while dipolar interactions simultaneously lead to field-induced ordering. 3 This results, for example in magneto-rheological and other properties which are of strong interest as the viscosity sensitively depends on external magnetic fields. 4 In particular, under the influence of shear, a torque is applied to the particles, leading to a field-induced viscosity anisotropy, as has been observed in a ferrofluid based on nanodisc cobalt particles.…”
Section: Introductionmentioning
confidence: 87%
“…During magnetic field directed self-assembly, the dipole–dipole interaction between magnetic particles or magnetic fluid droplets builds arrays of chain-like clusters that can span over a long distance at the microscale along the generated flux lines of the magnetic source. 28,29 The density of these flux lines is dependent on both the size and strength of the magnetic field; 30 therefore, the chain length, thickness, and gaps between them can be controlled by suitably selecting the magnetic field strength, orientation, and distance from the subject. Additionally, these arrays of chains must be immobilized on the substrate, either by drying or curing an aqueous polymer.…”
Section: Introductionmentioning
confidence: 99%